A New Thermodynamics - Mayhew, Kent W. (IJRDO-Journal of Applied Science, 2016)
Accepting that expanding systems must upwardly displace Earth’s atmosphere’s weight, and that this signifies lost work, renders most useful processes irreversible. This simple realization has not been properly addressed in thermodynamics, allowing ill-conceived second law based explanations to prevail. We will discuss how this mistake originates with Clausius’ theorem, and continues with Boltzmann’s entropy. We will discuss why we can never extract systems as much work from a system as the thermal energy that we put in. Then we will discuss why the traditional treatment of partial differentials remains so troublesome, and then provide a simpler understanding of free energies, which will lend itself to a better possible interpretation of entropy, one that removes our reliance on the second law. Ultimately, thermodynamics could be a simple constructive science. Our new interpretations may also have ramifications to our consideration of global warming.